Glucose Metabolism via the Entner-Doudoroff Pathway in Campylobacter: A Rare Trait that Enhances Survival and Promotes Biofilm Formation in Some Isolates - Vegge, Christina S.; Jansen van Rensburg, Melissa J.; Rasmussen, Janus J.; Maiden, Martin C. J.; Johnsen, Lea G.; Danielsen, Morten; MacIntyre, Sheila; Ingmer, Hanne; Kelly, David J. (Frontiers in Microbiology, 2016)
Isolates of the zoonotic pathogen Campylobacter are generally considered to be unable to metabolize glucose due to lack of key glycolytic enzymes. However, the Entner-Doudoroff (ED) pathway has been identified in Campylobacter jejuni subsp. doylei and a few C. coli isolates. A systematic search for ED pathway genes in a wide range of Campylobacter isolates and in the C. jejuni/coli PubMLST database revealed that 1.7% of >6,000 genomes encoded a complete ED pathway, including both C. jejuni and C. coli from diverse clinical, environmental and animal sources. In rich media, glucose significantly enhanced stationary phase survival of a set of ED-positive C. coli isolates. Unexpectedly, glucose massively promoted floating biofilm formation in some of these ED-positive isolates. Metabolic profiling by gas chromatography-mass spectrometry revealed distinct responses to glucose in a low biofilm strain (CV1257) compared to a high biofilm strain (B13117), consistent with preferential diversion of hexose-6-phosphate to polysaccharide in B13117. We conclude that while the ED pathway is rare amongst Campylobacter isolates causing human disease (the majority of which would be of agricultural origin), some glucose-utilizing isolates exhibit specific fitness advantages, including stationary-phase survival and biofilm production, highlighting key physiological benefits of this pathway in addition to energy conservation.